2021
DOI: 10.3390/molecules26092815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin and Ferulic Acid on the Folding of Amyloid-β Peptide

Abstract: The polyphenols curcumin (CU) and ferulic acid (FA) are able to inhibit the aggregation of amyloid-β (Aβ) peptide with different strengths. CU is a strong inhibitor while FA is a weaker one. In the present study, we examine the effects of CU and FA on the folding process of an Aβ monomer by 1 µs molecular dynamics (MD) simulations. We found that both inhibitors increase the helical propensity and decrease the non-helical propensity of Aβ peptide. They prevent the formation of a dense bulk core and shorten the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…The findings of our research on the binding interactions between compounds 1 – 4 and Aβ42 could be relevant in future research, such as the development of more effective Aβ42 aggregation inhibitors. These results agree well with previous published MD simulations of β-amyloid peptides [ 37 , 38 , 39 , 40 ], thereby offering promising leads towards development of potential therapeutics for AD.…”
Section: Resultssupporting
confidence: 92%
“…The findings of our research on the binding interactions between compounds 1 – 4 and Aβ42 could be relevant in future research, such as the development of more effective Aβ42 aggregation inhibitors. These results agree well with previous published MD simulations of β-amyloid peptides [ 37 , 38 , 39 , 40 ], thereby offering promising leads towards development of potential therapeutics for AD.…”
Section: Resultssupporting
confidence: 92%
“…Complementing experiments, computational studies reinforce the fact that curcumin and its products disaggregate and destabilize Aβ protofibrils and fibrils (12,13,(43)(44)(45)(46)(47)(48), deform the β-sheet structure in Aβ 42 dimers (49) and also form numerous interactions with the Aβ monomer (17,50,51). Salamanova et al found that curcumin and ferulic acid increase the helical content of the Aβ 42 peptide (17). A recent computational study consisting of docking followed by multi-ns MD simulations of curcumin and a hexamer peptide model of Aβ 42 fibril showed that curcumin partly dissociates the tip peptide of the Aβ 42 fibril by disrupting the β-sheet within the 12 VHHQKLVFF 20 sequence (43).…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, preventing or reducing the aggregation of the Aβ is an effective therapeutic strategy against AD. In recent years, small molecules have been developed as inhibitors to intervene in the formation of higher order aggregates of Aβ (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FA exhibits a wide range of biological activities but is best known for its ability to neutralize reactive oxygen species (ROS) [ 7 , 8 ]. However, recent studies have shown FA has diverse pharmacological effects such as anti-diabetic [ 8 , 9 ], and anti-bacterial effects against E. coli , Helicobacter pylori , and Shigella sannei [ 10 ], neuroprotective effects, especially in the context of amyloid β protein toxicity [ 11 , 12 , 13 , 14 , 15 , 16 ], a brightening effect on skin [ 17 ], and anti-cancer effects [ 18 , 19 , 20 ]. In addition, FA has been reported to induce hypoxia and enhance the angiogenesis of human umbilical vein endothelial cells (HUVEC) by increasing the expressions of HIF-1α and vascular endothelial growth factor (VEGF) [ 21 ] and to specifically enhance the neurogenic differentiations and survivals of different types of stem cells in vitro and in vivo [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%